The Call of the Wild - "London, Jack" (Longman Group Ltd: Harlow, 1997)
Stolen from his life as a beloved pet, Buck must learn to adapt to abuse as a Klondike sled dog, to life with a loving master, John Thornton, and finally, when Thornton dies, to life in the wild as a leader of the wolf pack
Keywords: Adventure stories